Oficinas sobre sexualidade com adolescentes: um estudo de caso - Silva, Caio Samuel da [UNESP]; Brancaleoni, Ana Paula Leivar [UNESP]; Oliveira, Rosemary Rodrigues de [UNESP] (My University, 2010)
Adolescents are commonly seen in a “sexless” way so that when the first sexual expressions appear in our young people they are permeated by worry and fear. In this context, the school spread the vision of sex and sexuality, as hazardous due to risks of sexually transmitted diseases and unwanted pregnancy. Thus, seeking to encourage reflection on the part of adolescents with regard to sexual life, workshops were developed with 15 students in a seventh grade student at a state school in the city of Jaboticabal, São Paulo. The findings of this research indicate that adolescents have conceptions of sexuality marked by repression, including the maintenance of sex roles traditionally established. The implementation of interventions in the form of workshops revealed that the group has become an area that favors the reconstruction and rebuilding of meanings through the questions and judgment of values and attitudes socially imposed.

Os adolescentes são vistos comumente de maneira “assexuada” de modo que o aparecimento das primeiras manifestações sexuais em nossos jovens é permeado por preocupação e receio. Neste contexto, a escola dissemina a visão do sexo e da sexualidade, como perigosos devido aos riscos das doenças sexualmente transmissíveis e à gravidez indesejada. Desta maneira, como intuito de favorecer a reflexão por parte dos adolescentes no que se refere à vivência da sexualidade, desenvolvemos oficinas junto a 15 alunos de uma sétima série do Ensino Fundamental de uma Escola Estadual do município de Jaboticabal, São Paulo. Os achados desta pesquisa indicam que os adolescentes possuem concepções de sexualidade marcadas por repressões, além da manutenção dos papéis sexuais tradicionalmente estabelecidos. A realização das intervenções na forma de oficinas revelou que o grupo tornou-se um espaço favorecedor da reconstrução e recriação de significados através de questionamentos e do julgamento de valores e atitudes socialmente impostos.
Workshops on sexuality with adolescents: a case study
Keywords: Sexuality; Adolescence; Workshops; School; Sexualidade; Adolescência; Oficinas; Escola